Cleaning Fungal Stains on Cotton and Wood-containing Paper Using Protease - Mohamed Zidan Mohamed Salem; Wael S. Mohamed; Olfat Ahmad; Rawan Ahmed; Naglaa Khaled; Nada Abo El-Makarem; Nora Fawzy; Rasha Sadek; Rushdya R. A. Hassan; Maximilian Lackner (BioResources, 2025)
Protease enzyme at concentrations of 50, 75, and 100 U (μmol/min), in both solution and paste form, was evaluated for cleaning stains caused by Aspergillus flavus. This applied study was conducted on paper sheets that had been formed from either cotton or wood-derived cellulose fibers. After cleaning, the infected samples were examined and analyzed to identify any changes and assess the effectiveness of the cleaning process. Color change, digital microscopy, ATR-FTIR, scanning electron microscopy, and pH measurement were employed. The results confirmed that the most effective treatment was the enzyme paste form at 50 and 75 U, as this was able to remove existing fungus spots on the surface or permeate within the fibers. IR spectroscopy confirmed that the chemical composition of both cotton and wood paper remained unchanged. Conversely, there was a significant increase in the characteristic vibrations of water and the crystallization sites of cellulose at the wavenumber of 1300 cm-1.